Sexual abuse of the girl-child: implication for counselling and educational practices (2015)
Child sexual abuse though not new in the contemporary society has in recent years exploded into public awareness with several cases reported in newspapers, magazines, and television features. This explosion of information suggests that sexual abuse of children is becoming much more common and more damaging to individuals and to society and therefore remains an issue of social concern. It is on this premise that this paper discusses the meaning, prevalence, impacts, disclosure and treatment of victims of child sexual abuse. It further enunciates the roles of the school and counselling psychologist in developing strategies geared towards obliterating the social stigma that may possibly result from reported cases in schools to enhance the educational performance of the girl child